2003
DOI: 10.1177/089686080302300507
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Function and Assessment of Reference Values Using a 3.86% Glucose Solution

Abstract: Background The most widely used peritoneal function test, the peritoneal equilibration test (PET), is performed with a 2.27% glucose solution. Recently, the International Society for Peritoneal Dialysis committee on ultrafiltration failure (UFF) advised performing the test with 3.86% glucose solution because it is more sensitive for detecting clinically significant UFF. Because no reference values for this test were available, we analyzed the results of standard peritoneal permeability analyses (SPAs) using 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 21 publications
4
95
2
3
Order By: Relevance
“…The reference times for obstetric intervention (from AS or feet of the calf appearance to birth) were estimated based on the mean ± 2 SD (Wenz et al, 2011) of unassisted births (eutocia). In addition, the upper limits of 95% CI (Smit et al, 2003) were reported for unassisted (eutocia) and assisted births (dystocia). The 95% CI was computed by including the CL option in the LSMEANS statement.…”
Section: Discussionmentioning
confidence: 99%
“…The reference times for obstetric intervention (from AS or feet of the calf appearance to birth) were estimated based on the mean ± 2 SD (Wenz et al, 2011) of unassisted births (eutocia). In addition, the upper limits of 95% CI (Smit et al, 2003) were reported for unassisted (eutocia) and assisted births (dystocia). The 95% CI was computed by including the CL option in the LSMEANS statement.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1990, a SPA was performed yearly to assess peritoneal transport characteristics (16,17). Only SPAs using solutions containing 3.86% glucose were selected for this study.…”
Section: Standard Peritoneal Permeability Analyses (Spa)mentioning
confidence: 99%
“…2 Water, sodium, and small solute transports can all be affected by this limitation. [3][4][5][6][7] The worst functional consequence is UF failure, which results in extracellular volume overload, increased cardiovascular risk, and the restriction for technique continuity. [8][9][10][11] Functional deterioration of the peritoneum is related to the damage induced by components of PD fluids, most likely pH, glucose, and glucose degradation products.…”
mentioning
confidence: 99%